020 Best Practices and Performance Measures for Systemic Treatment Perscriber Order Entry Systems (STCPOE) in Chemotherapy Delivery. (15th August 2013) - Kukreti, V; Cheung, A; Hertz, S; Kaizer, L; Lankshear, S
Abstract : Background: While information technology (IT) has the potential to improve the quality and safety of patient care, solutions such as computerised physician order entry (CPOE) are often designed and executed without end-user involvement and lack performance measures for monitoring quality and impact. To address this gap, an evidence based guideline for systemic treatment (ST) CPOE was developed incorporating both clinical and technological best practices. Performance measures for monitoring clinical impacts and system functionality were also developed. Context: The ST CPOE guideline was developed by a panel of physicians, nurses, pharmacists, IT specialists and human factors experts. Two Expert Panels (i.e. Clinical and Technology) were convened, to review and provide feedback on guideline content. Description of Best Practice: The guideline contains two distinct yet interconnected parts: clinical practice (e.g. error prevention, utilisation, clinical decision support), and technology requirements (e.g. usability, system integration, effective alerts). Also included are evidence based indicators to support the evaluation of ST CPOE systems and indicators reflecting clinician practice and patient outcomes. Quality monitoring of ST CPOE utilisation reveal that 75.5% of all chemotherapy visits are being supported by an ST CPOE system. A provincial evaluation of existing ST CPOE systems against the technology best practices is currently underway. Lessons for Guideline Developers, Adaptors, Implementers, and/or Users: This innovative guideline focuses on clinical practice driving IT solutions, not the other way around. A priori commitment to indicator development allowed for expanding beyond describing best practices to including indicators for monitoring progress toward achieving best practice, thus increasing relevance and uptake by end users.